Nutritional deficiencies and abortions in sheep and goats: An in-depth study from East Azerbaijan Province, Northwest Iran - Hassan Sadri; Monireh Khordadmehr; Hamid Akbari; Jafar Shirazi; Yaser Jafari-Khataylou; Saba Eskandari; Bahareh Sadat Mirarabshahi; Ali Abdolmaleki (PLoS ONE, 2025)
Vitamin and mineral levels in sheep and goat herds experiencing abortions in East Azerbaijan, northwest Iran, were studied. Between November 2023 and February 2024, 373 blood samples and 62 samples from aborted fetuses in various cities were collected. To find out whether a lack of selenium and copper in mothers led to heart and brain problems in their fetuses. Sheep and goats were mainly raised in a semi-intensive system, grazing from spring to mid-autumn and keeping indoors during winter. Sheep and goat flocks were categorized by size: small (1–100 sheep), medium (101–300 sheep), and large (over 300 sheep). The data show significant deficiencies in essential vitamins and minerals, affecting animal health and reproduction. A notable lack of vitamin A was observed in Bostan Abad. Widespread vitamin D deficiency was noted, especially severe in Jolfa, suggesting diet inadequacies despite enough sunlight. A slight deficiency of vitamin E was found, alleviated through farmers’ supplements helped some. Calcium and phosphorus deficiencies, particularly calcium, were also major concerns. Copper and zinc shortages were common across different cities. Aborted fetuses from copper-deficient mothers showed brain tissue damage, like Wallerian degeneration and neuronal necrosis. Severe iodine deficiency was observed in Marand and Khoda Afarin, risking thyroid and reproductive health and function. More than 87% of samples revealed significant selenium deficiency, indicating a need for supplementation. Pathological studies showed heart tissue damage in aborted fetuses from selenium-deficient mothers, including fragmentation, calcification, and necrosis. These results highlight the need for proper nutritional interventions and regular monitoring of vitamin and mineral levels to fix deficiencies. Proper nutrition in mothers is crucial for lowering abortion risks and fetal developmental issues. Our data highly recommend dietary changes and balanced vitamin and mineral supplements in the studied province, considering local factors such as soil quality, pasture, and crop residues.